Application of Realistic Mathematics Learning Approach to Improve Geometry and Measurement Learning Outcomes Of Aquaculture Students - Edo, Sri Imelda; Renoat, Emi (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This study aims to improve the achievement of students in aquaculture technology study program (TBP) for geometry and measurement subject through Indonesian Realistic mathematics Education (PMRI) approach using aquaculture context. This research used mixed method, namely classroom action research method and pre-experimental research methods with One Group Pretest-Posttest Design. The CAR method was used to find out how to improve student achievement in geometric and measurement topic for students of TBP study program in state polytechnic of Agriculture Kupang using PMRI approach. Meanwhile, the One Group Pretest-Posttest Design method was used to test whether there were significant differences of students’ achievement before and after the implementation of PMRI approach using aquaculture context. This research was conducted in TBP study program, Fisheries and Marine Department, state polytechnic of Agriculture Kupang. The research subjects consisted of all 67 students in semester 1 of the 2019/2020 academic year of TBP study program. The results showed that the implementation of PMRI Learning Approach using aquaculture Context was able to improve student achievement of the TBP study program, Fisheries and Marine Department, State Polytechnic Of Agriculture Kupang, where the percentage of classical completeness increase from 40.30% in the 1st cycle, 54% in the second cycle, and 88.05 % in the third cycle. While the results of the statistical test showed Sig. (2-tailed) or p-value <0.05 so H0 is rejected and Ha is accepted, meaning that there are significant differences in student achievement before and after the implementation of PMRI learning approach using aquaculture context